Accounting for managers - Kuppapally, Jelsy Joseph
This book strives to make Accounting intelligible and easily comprehensible to students. The text gives a comprehensive coverage of the three branches of Accounting Financial Accounting, Management Accounting, and Cost Accounting. It focuses on the various methods and techniques followed in the Management Reporting System. The text deals, in detail, with various accounting transaction procedures, methods of costing, ratio analysis, budgeting, forecasting, accounting errors, funds flow and cash flow statements, trial balance and balance sheet, and so on. It equips the students with the knowledge in the preparation, analysis, evaluation, and interpretation of financial statements, which will enrich their managerial competence and decision-making skills.